PENGARUH BUDAYA ORGANISASI DAN PERILAKU KEWARGAAN ORGANISASI TERHADAP PERSEPSI EFEKTIVITAS SEKOLAH PADA SUATU SEKOLAH KRISTEN TANGERANG [THE EFFECT OF ORGANIZATIONAL CULTURE AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR ON THE PERCEIVED SCHOOL EFFECTIVENESS AT A CHRISTIAN HIGH SCHOOL IN TANGERANG] - Iwan Seciady; Niko Sudibjo (Polyglot, 2020)
The researcher’s observations at XYZ Christian high school in Karawaci showed that strong communication channels between school leaders and employees appeared to be lacking. A pre-research questionnaire showed two kinds of employees’ perceptions of the school’s effectiveness, namely positive and negative. Thus, the researcher wanted to discover what factors existed in the school that influenced the perceived school effectiveness, especially related to the communication patterns of school leaders, the organizational culture of the school, and the organizational citizenship behavior of each teacher. The research subjects were 62 employees who worked at the school. The research design used was a regression study with a quantitative approach. The results showed that the school leaders’ communication patterns, the school’s organizational culture, and the organizational citizenship behavior of the teachers influenced the perceived school effectiveness positively.BAHASA INDONESIA ABSTRACT: Observasi peneliti terhadap sekolah Kristen XYZ di Karawaci memperlihatkan kecenderungan bahwa sekolah tidak memiliki ragam saluran komunikasi pemimpin sekolah yang kuat kepada para pihak karyawan, namun pra-penelitian memperlihatkan terdapat dua macam persepsi karyawan sekolah mengenai efektivitas sekolah SMA XYZ, yaitu perspektif positif dan perspektif negatif.  Dengan demikian, peneliti ingin mencari tahu pengaruh setiap faktor-faktor yang ada di dalam sekolah ini khususnya terkait dengan budaya organisasi pada sekolah dan perilaku kewargaan organisasi dari setiap guru terhadap persepsi efektivitas sekolah SMA XYZ tersebut. Subyek penelitian berjumlah 62 karyawan yang bekerja di SMA XYZ. Desain penelitian yang digunakan adalah penelitian regresi dengan pendekatan kuantitatif.Hasil penelitian memperlihatkan bahwa terdapat pengaruh positif budaya organisasi dan perilaku kewargaan organisasi terhadap persepsi efektivitas sekolah.